Penilaian Dan Pengukuran Biaya Terkait Kualitas Dalam Usaha Mengelola Dan Mengendalikan Kualitas Produk - Retno Nurasisyah; Firda Indah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to explore the importance of assessing and measuring quality-related costs in efforts to manage and control product quality. Through literature analysis and case studies, this research highlights the role of quality-related costs in management decision making regarding product quality. The findings from this research can provide valuable insight for business practitioners in optimizing product quality management and control by considering cost aspects.